Anti-inflammatory Effects of Persimmon (Diospyros kaki L.) in Experimental Rodent Rheumatoid Arthritis. (1st November 2020) - Direito, Rosa; Rocha, João; Serra, Ana-Teresa; Fernandes, Adelaide; Freitas, Marisa; Fernandes, Eduarda; Pinto, Rui; Bronze, Rosário; Sepodes, Bruno; Figueira, Maria-Eduardo
Abstract: Persimmon ( Diospyros kaki L.) fruits are used in traditional medicine largely due to their claimed beneficial effects on human health. The aim of this work was to evaluate the anti-inflammatory activity of a persimmon extract in rats with collagen-induced arthritis (CIA). CIA was induced in Wistar rats through an intradermal injection of an emulsion of bovine type II collagen (CII) in complete Freund's adjuvant (FCA). Macroscopic evidence of CIA first appeared as periarticular erythema and edema in the hind paws. The incidence of CIA was 100% by day 27 in the CII-challenged rats, and the severity of CIA progressed for 35 days. Radiographs revealed focal resorption of bone, with osteophyte formation in the tibiotarsal joint and soft tissue swelling. The histopathologic features included erosion of the cartilage at the joint margins. The persimmon extract showed an anti-inflammatory effect given the significant reduction in both the edema volume and radiological alterations attributed to CIA in the bone. We demonstrate that the administration of persimmon extract attenuates the degree of chronic inflammation and tissue damage characteristic of CIA in rats, most probably by the potent antioxidant characteristics of the extract.